The constellations of child fostering in Kenya: Considering location and distance - Cassandra Cotton; Clement Oduor (Demographic Research)
BACKGROUND: While studies provide context on why mothers foster-out children, there is little discussion about where children reside, transitions in children’s living arrangements over time, distance between fostered children and their mothers, and how such distance might influence mothers’ relationships with children. OBJECTIVE: We aimed to: (1) examine the geographical location of fostered children and distance from mothers, (2) establish who fosters children and the mothers’ relationships with caregivers, (3) determine transitions in children’s fostering arrangements, including mobility within kin networks, and (4) explore mothers’ perceptions of distance, location, and barriers to contact with fostered children. METHODS: We used innovative kinship-network data and in-depth interviews with mothers who have fostered-out children in Kenya. We mapped locations of fostered-out children using geo-coded data, determining ‘hot spots’ while exploring distance from mothers, and analyzed qualitative and quantitative data to examine mothers’ perceptions of distance as a barrier to maternal–child relationships. RESULTS: Fostered children live primarily in rural Kenya, and there is substantial fluidity in children’s living arrangements. Mothers’ relationships and contact with children are impacted by location and distance. CONTRIBUTION: Our study highlights kinship linkages and child fostering over time and space. It suggests vital areas in future research on fostering and kinship more broadly and demonstrates the possibility of narrowing the focus to collect more insightful data. It provides evidence on fostering experiences while accurately capturing children’s transitions over time and within kin networks. The study paints a more complete picture of child fostering complexities and how they rely on the constellations of available kin.